Congestion control in named data networking – A survey - Ren, Yongmao; Li, Jun; Shi, Shanshan; Li, Lingling; Wang, Guodong; Zhang, Beichuan (Computer communications, 2016)
As a typical Information Centric Networking, Named Data Networking (NDN) has attracted wide research attentions in recent years. NDN evolves today's host-centric network architecture TCP/IP to a data-centric network architecture. It turns the end-to-end connection-oriented transport of TCP/IP into receiver-driven connectionless transport. Compared with the traditional TCP/IP networking, the transport in NDN has new characteristics: Receiver-driven, One-Interest-one-Data, Multi-Source, and Multi-Path. These distinguished features pose new challenges to NDN congestion control mechanisms. This paper presents a comprehensive survey of state-of-art techniques aiming to address these issues, with particular focus on improving the effectiveness of congestion detection and the efficiency of Interest rate shaping. As a new research area, this paper also points out research challenges and open issues in this subject.